ISTIQRĀ’ DAN PENERAPANNYA TERHADAP AL-QAWĀ`ID AL-FIQHIYYAH - Safriadi Safriadi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
Al-Qawā‘id al-Fiqhiyyah is a general theory of Islamic law produced through the istiqra’ '(induction) process. But such affirmation has never been done and to do so requires adequate evidence and analysis of the working techniques of al-Qawā‘id al-Fiqhiyyah. The author in this study conducted a study of al-Qawā‘id al-Fiqhiyyah compiled by Tāj al-Din al-Subki in his work al-Asybāh wa al-naẓā‘ir. This research is a library research with an approach to the philosophy of Islamic law. The results state that the work method istiqrā ', namely the principle of thinking that draws conclusions from empirical research on particular events into a unity of universal law. This legal conclusion will be applied (prediction) to the object of the problem which still has relevance to the particular things mentioned earlier. The role of istiqrā 'in the preparation of al-Qawā'id al-Fiqhiyyah in particular al-Qawā'id al-Asāsiyah is to take the essence of the rules of fiqh (furū') which have similarity to illat or wisdom which results are then formulated in general rules which includes cases of particular law below. Besides that, each rule always includes exceptions (muśtanāyat). This form of exception is in terms of the problem of induction in logic.